Avaliação da durabilidade de concretos produzidos com agregado miúdo reciclado de cerâmica vermelha - MORAES, Ruan Fabrício Gonçalves (Universidade Federal do Pará, 2018)
The generation of waste from civil construction (WCC) in Brazil and in the world are of great proportions. However, its reuse does not occur in the same proportions that are generated by construction, is added to this, the need to find solutions for the landfilling of these wastes, unsustainable consumption of natural resources, where deposits already present signals aggregate shortage. Therefore, the use of red ceramic as recycled aggregate, reduces costs for the production of concrete, brings awareness of environmental cooperation and sustainability. In this scenario, the literature is still scarce in relation to the concrete durability properties for this kind of aggregate. Thus, this study aimed to improve and disseminate knowledge about these waste in construction. To this end, mixtures were made with water / cement ratio of 0.45; 0.55 and 0.65, where the aggregate has been replaced by natural fine ceramic aggregate in 0%, 12.5% and 25%, each percentage was subjected to pre-wetting rate of 40%, 60% and 80%. Subsequently, the durability of concrete produced with fine ceramic aggregate (FCA) was evaluated through capillary absorption, carbonation, electrical resistivity and chloride ion penetration. With the results obtained it can be concluded that the slump test was satisfactory in most mixtures, with respect to durability, in general, all mixtures with ceramic recycled aggregate had higher durability than the reference, especially in mixtures with 25% AMC. Pre-wetting rates were effective in most mixtures, showing satisfactory influence on the final results in all tests. So it managed to show great feasibility of using this waste in concrete, improving their performance.